Asteraceae Diversity and A New Record For Java at Citalahab Village, Gunung Halimun-Salak National Park - Dee Dee Al Farishy; Andi Salamah (Jurnal Biologi Tropis, 2021)
Asteraceae is the second largest plant family in the world. The family member has reached 227 species in Java. However, there is no current record of wild Asteraceae around local village within Gunung Halimun-Salak National Park. This study is to provide current Asteraceae species data and the threat for the conservation area. Explorative method has been conducted in 6 sites. The result shows that there are 20 species found with the tribes composition are 8 Heliantheae, 6 Eupatorieae, 3 Senecioneae, 1 Astereae, 1 Cichorieae, and 1 new record Vernonieae in Java. Key identification for species are provided and the new record has been described. Most species categorized as introduced with several other categorized as invasive alien species. In conclusion, numbers of Asteraceae family has been recorded with some potential ivansive threat in Gunung Halimun-Salak National Park. Regular population control and treatment are recommended in order to protect native species in the conservation area.